Developing local-based content supplementary reading material for senior high school in Lubuklinggau - Indriani, Indriani; Seli, Sastika; Syafitri, Dewi (Universitas Sarjanawiyata Tamansiswa, 2023)
The aim of this research was to find out the validity, practicality, and effectiveness of a developed book entitled Developing Local Based Content Supplementary Reading Material for Senior High School in Lubuklinggau. In conducting the research, Research, and Development, written by Branch (2009), consisting of analysis, design, development, implementation, and evaluation (ADDIE) was used as steps in developing the product; meanwhile, Formative Evaluation written by Tessmer (1993) was used to evaluate the data. To determine the validity of the book, three experts were included to review the product, namely a content expert, an instructional design expert, and a layout quality expert. To determine the practicality and effectiveness of the product, three students were involved in a one-to-one trial, six students were involved in a small group trial, and ten students were involved in a field test. The practicality and effectiveness values were obtained from tenth-grade students in Senior High School number 1 Lubuklinggau in the academic year 2021-2022 which were taken as subjects of the research. To collect the data, a questionnaire, interviews, and a test were used. The collected data were analyzed qualitatively for the interview and quantitatively by using average scores for the questionnaire and the test. After all, the data had been analyzed, it could be concluded that the product as a book was categorized as highly valid with an average score of 3.76, categorized as very highly practical with an average score of 4.67 at the one-to-one trial and 4.32 at small group trial, and categorized very highly effective with average score 90.